Determination Of Site Selection Criteria For Hospitals Cumayeri Sample (Duzce) - Uzun, Serir; Aydın, Arzu (Bartın Üniversitesi, 2021)
Success in hospital planning and design depends on choosing the appropriate hospital location. However, there are not enough studies to determine the site of the hospital. Geographic Information Systems is a tool that shows superiority over traditional methods in the planning stage of site selection studies. The aim of this study is to investigate and evaluate the natural and cultural characteristics of the area in the Cumayeri district of Düzce, and to provide an environmentally friendly, ecologically based, accurate assessment of the area with the help of GIS and to guide the selection of a qualified hospital area. In this study, data of geology, topography, soil and forestry maps were used. On the other hand, maps containing data such as hydrology, slope, view, land use, road network, and settlement areas were produced. In the light of all these data, “hospital suitability and landscape sensitivity maps” were created. An "optimal hospital area map" was created with the holistic evaluation of these two maps. Arc GIS 10.1 program was used in the production and data processing of all these maps. Then, according to the determined criteria, suitable areas for the establishment of a city hospital in Cumayeri district of Düzce province were determined.

Hastane planlama ve tasarımında başarı uygun hastane yeri seçimine bağlıdır. Ancak hastane yer seçiminin belirlenmesi konusunda yeteri kadar çalışma bulunmamaktadır. Coğrafi Bilgi Sistemleri yer seçim çalışmalarının planlama aşamasında, geleneksel yöntemlere oranla üstünlük gösteren bir araçtır. Bu çalışmada Düzce İli Cumayeri ilçesinde alanının doğal ve kültürel özelliklerinin araştırılıp, değerlendirilmesi yapılarak çevreye uyumlu, ekolojik temelli, alanın en doğru şekilde değerlendirilmesinin CBS yardımı ile yapılarak nitelikli bir hastane alanı seçimi gerçekleştirilmesinde yol gösterici olması amaçlanmıştır. Çalışmada temel olarak, jeoloji, topografya, toprak ve amenajman haritalarının verileri kullanılmıştır. Diğer taraftan hidroloji, eğim, bakı, arazi kullanımı, yol ağı, yerleşim alanları gibi verileri içeren haritalar üretilmiştir. Tüm bu veriler ışığında “hastane uygunluk ve peyzaj hassasiyet haritaları” oluşturulmuştur. Bu iki haritanın bütüncül değerlendirilmesi ile “optimal hastane alan haritası” oluşturulmuştur. Tüm bu haritaların üretiminde ve veri işlemeleri aşamasında Arc GIS 10.1 programı kullanılmıştır. Daha sonra belirlenen kriterlere göre Düzce İli Cumayeri ilçesinde şehir hastanesi kurulması için uygun alanlar ortaya konulmuştur.
Şehir Hastaneleri Yer Seçim Kriterlerinin Belirlenmesi Cumayeri Örneği (Düzce)
Keywords: Forest Industry Engineering; Orman Endüstri Mühendisliği